Flexible Interventions to Increase Family Engagement at Natural History Museum Dioramas. (October 2016) - Knutson, Karen; Lyon, Mandela; Crowley, Kevin; Giarratani, Lauren
Abstract: A research/practice collaboration designed, implemented, and tested strategies to facilitate family engagement with natural history dioramas. Across a series of design studies, 295 family groups with at least one adult and one child aged 4–18 were observed at a wildlife diorama of deer in their natural habitat. Each mini‐study tested a different intervention intended to encourage families to engage more deeply with the diorama. Compared to a baseline condition where families used the original diorama with no intervention, findings suggested that all interventions supported increased engagement, but that some interventions were more successful at engaging younger children, increasing conversations about biodiversity and ecosystems issues, or in developing science skills such as observation and classification. We make recommendations for supporting family learning at dioramas and also reflect upon how our research/practice partnership was vital to the work.